As chaves do Inferno: as múltiplas linguagens em Sandman, de Neil Gaiman - Cunha, Ana Carolina Moscardini (2018)
The present research presents how the multiple languages that are part of Sandman, by Neil Gaiman, simultaneously construct and reconstruct his work, showing how the gathering of visual and textual is intrinsically interconnected. From the study of ideas and writings by authors like Julia Kristeva, Mikhail Bakhtin, Graham Allem, Claus Clüver, Leo Hoek, Edgar Guimarães, Will Eisner, Scott McCloud, Giulio Argan and Heinrich Wöfflin it will be possible to trace and analyze the performance of the Arts presented in Sandman. This dissertation was divided in three chapters and the content of which one is as follows: in the first chapter there is a presentation of the plot of Sandman, in addition to a survey of the languages present in the work of Neil Gaiman; in the second chapter there is a study of critical fortune related to intertextuality and interdiscursivity. The third chapter will aim to recover what was presented in the first two and from the discussions contained in the previous chapters, to analyze how the multiplicity of languages is constructed. At the end of the third chapter, the final considerations of the dissertation will be presented.